Approaches to the epistemological analysis of the New Public Management - Carolina Yelicich (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2017)
As a course of action to overcome the crisis of the welfare state and supported by a neoliberal vision of the state administration, the New Public Management (NPM) was installed with greater or lesser intensity in many countries in different continents. In Latin America, this scheme of public policy relations had its highest expression in reform packages implemented during the 1990s. The substrate of the NPM is focused on the reorganization of public administration based on market, management, and competition to create an efficient and effective public administration at the lowest possible cost. This paper analyzes the fundamentals of the NPM, based on the theoretical and epistemological research in public policy models. It is intended to present some considerations about the theoretical and epistemological support of NPM and to identify some of the reasons for its intense implementation as a new scheme of organization and relationships in public administration in recent decades. Special attention is given to the penetration of NGP in the education sector, with an emphasis on the processes of school management. The text is based on a theoretical approach backed by a literature review and exploration of secondary sources.